Introduction. Understanding the 2018 Statewide Walkouts Contemporary Educator Movements: Transforming Unions, Schools and Society in North America (Part 2): Understanding the 2018 Statewide Walkouts - Dyke, Erin; Stark, Lauren Ware; Maton, Rhiannon (Critical Education, 2022)
This is the second of four issues in the special series investigating Contemporary Educator Movements: Transforming Unions, Schools, and Society in North America. This issue focuses on the “red” statewide K12 education strikes in the United States in the spring of 2018, contributing substantive analyses of the relatively understudied contexts of the walkouts for scholars and organizers. Together, the pieces in this issue suggest the importance of attending to the unique and deeply contested political geographies of the nation’s more rural regions and the significance of these regions to contemporary educator struggles.